Relationship of Early Postoperative Dysrhythmias and Long-Term Outcome after Resection of Non-Small Cell Lung Cancer - Amar, D. (Institutional Knowledge at Singapore Management University, 1996)
To determine whether supraventricular tachydysrhythmias (SVTs) occurring early after thoracic surgery for non-small cell lung cancer (NSCLC) are associated with poor long-term survival. Design : Prospective, cohort. Setting : Referral cancer center. Patients : Seventy-eight patients undergoing resection of NSCLC. Interventions : Examination of univariate and multivariate effects of factors that might influence long-term survival : advanced age, sex, perioperative chemotherapy, extent of pulmonary resection, tumor stage, and SVT occurrence. Results : In this group of patients, 10 of 78 (13%) developed early postoperative SVT. Log-rank analysis showed SVT occurrence (p=0.01), age of 70 years or older (p=0.04), and perioperative chemotherapy (p=0.005) to predict poor long-term survival. Multivariate Cox regression analysis identified SVT occurrence (p=0.007 ; relative risk [RR], 2.8 ; 95% confidence interval [CI], 1.3 to 6.1) and perioperative chemotherapy (p=0.004 ; RR, 2.6 ; 95% CI, 1.4 to 5.1) to be independently associated with decreased survival. No other clinical or laboratory characteristic tested differentiated those patients who did or did not develop postoperative SVT. Conclusions : Early SVT occurrence after resection of NSCLC is associated with poor long-term survival. Although the etiology for this is unclear, this intriguing observation, not previously reported (to our knowledge), may be used in larger trials examining the effects of these and other factors on survival from lung cancer surgery.